Phenolic Content, Antioxidant Capacity and In Vitro Glycemic Index of Traditional Noodle (EriSte) High in Plant-Based Protein and β-Glucan Content - Arer, Damla; Acar, Oguz; Ozkan, Kubra; Sagdic, Osman; Visioni, Andrea; Sestili, Francesco; Koksel, Hamit (WILEY, 2025)
Traditional noodle samples (eri & scedil;te) were supplemented with hull-less barley and lentil flours as the source of beta-glucan and protein at different ratios and their cooking quality, phenolic content, antioxidant capacity and estimated GI values were evaluated. The estimated GI of control eri & scedil;te produced from wheat flour was the highest (74.7), while GI of those supplemented with 15%, 30%, 45% barley or lentil flour were 68.7%, 66.0%, 61.2% and 67.5%, 63.8%, 60.6%, respectively. GI values of mixtures of barley and lentils flours (Mix-1-4 samples) were lower (58.9-61.0). All noodles supplemented with barley and/or lentil flours had medium GI values. The eri & scedil;te samples supplemented with 45% hull-less barley flour and Mix eri & scedil;te samples meet the requirements of FDA health claim (0.75 g beta-glucan per serving). Protein content of control sample was 16.30%, while those supplemented with lentil flour had higher protein contents (18.15%-22.36%). Hence, noodle samples supplemented with 30% and 45% lentil flour can be labeled as high protein and all other noodle samples can be labeled as source of protein according to EC Regulation because calories which can be received from proteins per serving are > 20% and > 12%, respectively. Significant increases were also observed in phenolic contents and antioxidant capacities of eri & scedil;te samples supplemented with barley/lentil flours.
Keywords: beta-glucan; eri & scedil; te; in vitro glycemic index; plant-based protein; traditional noodle; Food Science & Technology